Address Presenting the Eighth Annual Report - Black, Eugene R. (World Bank, Washington, DC, 2019)
Eugene R. Black, President of the International Bank for Reconstruction and Development, reviewed Bank lending and pleaded for member countries to release their local currency subscriptions to the use of the Bank. He mentioned his practice to visit for some time each year some part of the world, getting to know at first hand the economic and development problems of member countries. He discussed an indispensable element in the financing of long-term development which is the increased flow into the underdeveloped world of private investment capital from abroad. He described how the bulk of Bank's investment operations had been in the field of public utilities, especially of electric power, and Bank is constantly encountering the importance of power, even where Bank are financing projects outside the immediate power field. He concluded by saying that private capital would make a large contribution to Bank's investment, which would benefit recipient countries by helping to speed their development and to raise their productivity and their living standards.